2016
DOI: 10.1890/15-0202
|View full text |Cite
|
Sign up to set email alerts
|

Moderation is best: effects of grazing intensity on plant–flower visitor networks in Mediterranean communities

Abstract: The structure of pollination networks is an important indicator of ecosystem stability and functioning. Livestock grazing is a frequent land use practice that directly affects the abundance and diversity of flowers and pollinators and, therefore, may indirectly affect the structure of pollination networks. We studied how grazing intensity affected the structure of plant-flower visitor networks along a wide range of grazing intensities by sheep and goats, using data from 11 Mediterranean plant-flower visitor co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 80 publications
2
36
0
5
Order By: Relevance
“…In addition, bees and wasps might have a greater mobility (Torné‐Noguera et al ) and thus are less influenced by local disturbances. We need more information on the rewiring capacity of different flower visitor functional groups in face of a habitat disturbance (Burkle et al , Aguirre‐Gutiérrez et al , Lázaro et al ) as well as on the ultimate consequences of such rewiring for plant reproductive success. From a conservation viewpoint, monitoring these changes in natural communities could be highly relevant to the proposal of effective conservation strategies (Campos‐Navarrete et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, bees and wasps might have a greater mobility (Torné‐Noguera et al ) and thus are less influenced by local disturbances. We need more information on the rewiring capacity of different flower visitor functional groups in face of a habitat disturbance (Burkle et al , Aguirre‐Gutiérrez et al , Lázaro et al ) as well as on the ultimate consequences of such rewiring for plant reproductive success. From a conservation viewpoint, monitoring these changes in natural communities could be highly relevant to the proposal of effective conservation strategies (Campos‐Navarrete et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, flower visitor abundance and species richness have been shown to increase with floral abundance (Hegland and Boeke , Hagen and Kraemer ) and plant diversity (Potts et al , Ghazoul , Blüthgen et al 2007, Ebeling et al ). In general, there is still scarce information on how different pollinator functional groups can respond to habitat disturbance (Burkle et al , Aguirre‐Gutiérrez et al , Lázaro et al ) and how they change their interaction patterns with plants in the community (e.g. their rewiring capacity within the network).…”
mentioning
confidence: 99%
“…; Lázaro et al . ). Further, spatial planning and grassland management that increases spatial heterogeneity in the grazed area can be beneficial to pollinator diversity in regions adapted to grazing, such as those historically grazed by native large herbivores (Fuhlendorf & Engle ).…”
Section: Land Management To Increase Local Nesting and Foraging Resoumentioning
confidence: 97%
“…In the same study system, Lazaro et al. (2016b) further showed that intermediate grazing intensities create larger and more diverse pollination networks. Surprisingly, the effects of cattle grazing on managed honey bees are also poorly known; nevertheless, a few studies have shown the importance and positive contribution of Mediterranean rangelands to the availability of honey bee foraging plants (Petanidou and Smets ).…”
Section: Introductionmentioning
confidence: 84%